Olanzapine modulation of hepatic oxidative stress and inflammation in socially isolated rats - Todorović, Nevena; Gass, Peter (European journal of pharmaceutical sciences, 2016)
Olanzapine, an atypical antipsychotic, is efficient in stress associated psychiatric diseases, but its effect on the liver, a primary organ for drug activation and detoxification, still remains unclear. The effect of olanzapine administration (7.5mg/kg/day), on rat hepatic glutathione (GSH)-dependent defense and proinflammatory cytokines following 6weeks of chronic social isolation (CSIS), which causes depressive- and anxiety-like behavior in adult male Wistar rats, was investigated. The subcellular distribution of nuclear factor-κB (NF-κB), cytosolic inducible nitric oxide synthase (iNOS) protein levels and hepatic histological alterations were also determined. Decreased GSH content and glutathione reductase activity associated with increased catalase and glutathione S-transferase activity following CSIS indicated hepatic oxidative stress. Moreover, CSIS caused NF-κB nuclear translocation and the concomitant increase in iNOS together with increase in interleukin-1beta and tumor necrosis factor alpha protein levels, but no effect on interleukin-6. Olanzapine treatment suppressed NF-κB activation and iNOS expression and caused modulation of GSH-dependent defense systems but failed to reverse CSIS-induced increase in hepatic proinflammatory cytokines. Portal inflammation, focal hepatocyte necrosis and an increased number of Kupffer cells in CSIS rats (vehicle- or olanzapine-treated) were found. Olanzapine-treated socially reared rats showed portal inflammation and focal hepatocyte necrosis. Data suggest that CSIS compromised GSH-dependent defense, triggered a proinflammatory response and histological alterations in rat liver. Olanzapine treatment partially reversed the alterations in hepatic GSH-dependent defense, but showed no anti-inflammatory effect suggesting that it may provide protective effect against hepatic CSIS-induced oxidative stress, but not against inflammation.
Gesehen am 22.01.2019
Available online 19 October 2015